2017
DOI: 10.1101/126847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanopore Long-Read RNAseq Reveals Widespread Transcriptional Variation Among the Surface Receptors of Individual B cells

Abstract: Understanding gene regulation and function requires a genome-wide method capable of capturing both gene expression levels and isoform diversity at the single cell level. Short-read RNAseq, while the current standard for gene expression quantification, is limited in its ability to resolve complex isoforms because it fails to sequence full-length cDNA copies of RNA molecules. Here, we investigated whether RNAseq using the long-read single-molecule Oxford Nanopore MinION sequencing technology (ONT RNAseq) would b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 61 publications
1
51
0
Order By: Relevance
“…To identify transcript isoforms, we used the R2C2 reads as input into a revised version of the Mandalorion tool (v3, github) 10 . We detected 21,358 transcript isoforms expressed from 9,971 gene loci.…”
Section: Isoform Identification and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify transcript isoforms, we used the R2C2 reads as input into a revised version of the Mandalorion tool (v3, github) 10 . We detected 21,358 transcript isoforms expressed from 9,971 gene loci.…”
Section: Isoform Identification and Evaluationmentioning
confidence: 99%
“…However, evidence is accumulating that these epitopes might be absent in some transcript isoforms of these genes. Detailed analysis of this absence and possible consequences is hampered by the inability of RNA-seq to resolve transcript isoforms 10,15,16 . Determining isoform level transcriptomes of healthy and cancerous immune cells might therefore inform treatment decisions and future development.…”
Section: Introductionmentioning
confidence: 99%
“…To address these unknowns, we developed a straightforward and cost-effective approach using a long-read sequencing technology [32][33][34] . We combined long-range RT-PCR with long-read nanopore sequencing and a novel bioinformatics pipeline to characterise full-length CACNA1C coding sequences (CDSs) in post-mortem human brain.…”
Section: Introductionmentioning
confidence: 99%
“…The non-parametric approach to learning the read generating mechanism makes AIDE a data-driven method and does not depend on specific assumptions of the RNA-seq experiment protocols. Therefore, a natural extension of AIDE is to combine the short but more accurate reads from the second-generation technologies with the longer but more error-prone reads generated by new sequencing technologies such as PacBio (Rhoads and Au 2015) and Nanopore (Byrne et al 2017). Jointly modeling of the two types of reads using the AIDE method has the potential to greatly improve the overall accuracy of isoform detection (Fu et al 2018), since AIDE is shown to have better precision than existing methods, and longer RNA-seq reads capture more splicing junctions and can further improve the recall rate of AIDE.…”
Section: Discussionmentioning
confidence: 99%